(untitled) - DeVoss, Dànielle Nicole (San Francisco, 2010)
How to apply digital writing skills effectively in the classroom, from the prestigious National Writing Project As many teachers know, students may be adept at text messaging and communicating online but do not know how to craft a basic essay. In the classroom, students are increasingly required to create web-based or multi-media productions that also include writing. Since writing in and for the online realm often defies standard writing conventions, this book defines digital writing and examines how best to integrate new technologies into writing instruction. Shows how to integrate new technologies into classroom lessons. Addresses the proliferation of writing in the digital age. Offers a guide for improving students' online writing skills. The book is an important manual for understanding this new frontier of writing for teachers, school leaders, university faculty, and teacher educators.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Study and teaching,Rhetoric,Study and teaching,Composition and exercises,Dạy và học,Tu từ học,Dạy và học,Thành phần và bài tập